P114 Thermostable intravenous epoprostenol for the treatment of pulmonary arterial hypertension – a transition study. (12th November 2019) - MacLellan, A; Carson, K; Brewis, M; Johnson, M; McGettrick, M; McCaughey, P; Crozier, A; Thomson, R; Church, C
Abstract : Introduction and objectives: Epoprostenol is a synthetic prostacyclin analogue which has been used in the treatment of pulmonary arterial hypertension (PAH) for a number of years. To date, it has been the only disease targeted therapy to have demonstrated an overall survival benefit for PAH patients (Demerouti et al ., 2019). The previously available formulation of epoprostenol (Flolan 10.5) was thermolabile, meaning that it had to be prepared daily by patients and kept on ice to delay degradation. Recently a new formulation (Flolan 12) with greater thermostability has meant that these restrictions are no longer needed. The objective of our study was to transition patients onto Flolan 12 and examine for any safety issues associated with this transition, as well as looking at impact of quality of life (QoL), 6-minute walk distance (6MWD) and NT-proBNP. Methods: All patients in our unit receiving a stable dose of intravenous epoprostenol for at least 3 months as of November 2016 were included in the study (n=22). Over the next 12 months these patients were transitioned onto Flolan 12. We compared 6MWD, NT-proBNP and QoL measures prior to treatment transition and then at first routine clinical follow-up following transition. QoL was measured using the Emphasis-10 questionnaire. We also utilised a separate questionnaire which focused on the effect of epoprostenol use on activities of daily living. The was completed pre- and post-transition. Results: No safety issues were identified following transition to Flolan 12. No significant changes in QoL, 6MWD (see figure 1) or NT-proBNP were observed across the cohort following transition. All but one of the patients preferred the new formulation of epoprostenol. The one remaining patient expressed no preference. Conclusions: Analysis of QoL, 6MWD and NT-proBNP has shown no detrimental clinical effects from the transition to the new formulation. The new formulation of epoprostenol has been well received by our patients due to its convenience. Reference: DEMEROUTI, E., KARYOFYLLIS, P., MANGINAS, A., ANTHI, A., KARATASAKIS, G., ATHANASSOPOULOS, G. & VOUDRIS, V. 2019. Improving Survival in Patients with Pulmonary Arterial Hypertension: Focus on Intravenous Epoprostenol. Am J Cardiovasc drugs, 19, 99–105.